An Overlooked Prebiotic: Beneficial Effect of Dietary Nucleotide Supplementation on Gut Microbiota and Metabolites in Senescence-Accelerated Mouse Prone-8 Mice - Ding, Ting; Xu, Meihong; Li, Yong (Frontiers in Nutrition, 2022)
Nucleotides (NTs) are regulatory factors in many biological processes and play important roles in the growth, development, and metabolism of living organisms. We used senescence-accelerated mouse prone-8 (SAMP8) to investigate the effects of NTs on the gut microbiota and metabolites. And the promoting effect of NTs on the growth of a probiotic (Lactobacillus casei) was explored through in vitro experiments. The results showed that the sequencing depth of 16S rDNA covered all microbial species in the feces of SAMP8. Supplementation with exogenous NTs to the diet enhanced the diversity of the gut microbiota, reduced the abundance of bacteria with negative effects on the body (such as Verrucomicrobia, Ruminococcaceae, Akkermansia and Helicobacter), and increased the abundance of the microbiota, which had beneficial effects on the mice (such as Lactobacillus, Candidatus saccharimonas and Lachnospiraceae_NK4A136_group). Metabonomic analysis showed that NT deficiency in the diet significantly affected metabolites in the mouse feces. The metabolites in mice supplemented with NTs tended to be normal (SAMR1). The differentially expressed metabolites caused by NT addition are involved in various pathways in the body, including linoleic acid metabolism, vitamin B6 metabolism, and histidine metabolism. Correlation analysis revealed a significant correlation between the gut microbiota and differentially expressed metabolites caused by the addition of NTs. In vitro experiments showed that NTs significantly promoted the growth, secretion of biofilm and extracellular polymeric substance of L. casei. NTs also promoted the ability of the crude extract of L. casei to resist the secretion of Shigella biofilm. Thus, NTs can regulate the abundance of the gut microbiota and alter the metabolic expression of the intestinal microbiome.